Processing deceptive information in sports: Individual differences for responding to head fakes depends on the attentional capability of the observer. (November 2020) - Güldenpenning, Iris; Weigelt, Matthias; Memmert, Daniel; Klatt, Stefanie
Abstract: In team sports, players sometimes try to deceive their opponents by providing misleading information in order to gain a temporal advantage. Head-fakes are often applied when a player gazes in one direction, while passing/shooting the ball in another direction. The opponent is challenged to focus attention on the relevant information (i.e., pass direction), while ignoring the conflicting information (i.e., gaze direction). The present study aimed to identify the link between attentional capabilities and the effectiveness of head fakes. Twenty-seven novices performed in a basketball-specific head-fake task and in the attention-window task. A correlation between performances in both tasks revealed that participants with higher attentional capabilities were better able to focus their attention on the relevant feature (pass direction), when judging basketball situations, than participants with lower attentional capabilities. The results emphasize the relevance of high attentional capabilities in team sports and indicate that focusing one's attention to the pass direction poses a possibility of reducing the effects of head fakes. Highlights: Head fakes in basketball slow down the reaction in the observer. The challenge for the observer is to specifically attend the pass direction. Attentional capabilities correlate with the effectiveness of head fakes. The results emphasize the relevance of high attentional capabilities in team sports.